One-year recurrence of stroke and death in Lebanese survivors of first-ever stroke: Time-to-Event analysis - Boutros, Celina F.; Khazaal, Walaa; Taliani, Maram; Said Sadier, Najwane; Salameh, Pascale; Hosseini, Hassan (Frontiers in Neurology, 2022)
Background: Till date, despite the application of secondary prevention worldwide, first-ever stroke survivors remain at imminent risk of stroke recurrence and death in the short and long term. The present study aimed to assess the cumulative risk rates and identify baseline differences and stroke characteristics of Lebanese survivors. Methods: A prospective longitudinal study was conducted among survivors ≥18 years old who were followed-up for 15 months through a face-to-face interview. Kaplan-Meier method was used to calculate the cumulative rates of stroke mortality and recurrence. Cox-regression univariate and multivariable analyses were performed to identify the predictors of both outcomes. Results: Among 150 subjects (mean age 74±12 years; 58.7% men versus 44.3% women; 95.3% with ischemic stroke versus 4.3% with intracerebral hemorrhage), high cumulative risk rates of stroke recurrence (25%) and death (21%) were highlighted, especially in the acute phase. Survival rates were lesser in patients with stroke recurrence compared to those without recurrence (Log-rank test P<0.001). Older age was the main predictor for both outcomes (p<0.02). Large Artery Atherosclerosis was predominant in patients with stroke recurrence and death compared to Small Vessel Occlusion (p<0.02). Higher Mental Component Summary scores of quality of life were inversely associated with stroke recurrence (p<0.01). Lebanese survivors exhibited the highest percentages of depression and anxiety; elevated Hospital Anxiety and Depression Scale (HADS) scores were seen in those with stroke recurrence and those who died (≥80% with mean HADS scores≥8). Lower Mini-Mental State Examination scores at the acute phase increased the risk of both outcomes by 10% (p<0.03). Three out of thirteen mortalities (23.1%) presented with early epileptic seizures (p=0.012). High educational level was the protective factor against stroke recurrence (p=0.019). Administration of intravenous thrombolysis decreased the risk of both outcomes by 10% (p>0.05). Conclusion: Higher rates of stroke recurrence and death were observed in the first year following stroke in Lebanon.Various factors were identified as significant determinants. Thus, health care providers and officials in Lebanon can use these findings to implement effective preventive strategies to best address the management of these factors to reduce the stroke burden and improve short and long-term prognosis of stroke survivors.